RETRACTED: Impact of vitrification on human oocytes before and after in vitro maturation: A systematic review and meta-analysis. (August 2018) - Mohsenzadeh, Mehdi; Salehi-Abargouei, Amin; Tabibnejad, Nasim; Karimi-Zarchi, Mojgan; Khalili, Mohammad Ali
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editorial Board as the paper contains a significant number of similarities and word overlap with another paper published in Journal Cryobiology, representing duplication publication. The article (Effect of vitrification on human oocyte maturation rate during in vitro maturation procedure: A systematic review and meta-analysis [Cryobiology. Aug 2018; 83:84-89]) can be found here DOI:10.1016/j.cryobiol.2018.05.003 .